Orography‐Induced Atmospheric Small‐Scale Waves During Bora Using Lidar Observations and Numerical Simulations - Longlong Wang; Marija Bervida Mačak; Samo Stanič; Luca Patruno; Wenjun Dong; Daru Chen (Geophysical Research Letters)
Abstract Atmospheric flow of cold air over mountain barriers in the Alpine region often gives a rise to strong and gusty downslope wind, Bora. Such flows are often accompanied by atmospheric waves, generated by the flow passing an elevated barrier. Such phenomenon can only rarely be observed visually and can generally not be reliably reproduced by simplified numerical models. Orography‐induced atmospheric small‐scale waves were experimentally observed on 25 January 2019 during a Bora outbreak in the Vipava valley, Slovenia. A vertical scanning lidar, positioned at the lee side of the Trnovski gozd mountain and a fixed direction lidar, 5 km apart in the Vipava valley, were used to characterize the density field. The flow exhibited a stationary jump after the mountain ridge and, superimposed, an oscillatory flow pattern. High‐resolution numerical simulations complemented the observations and supported experimental results on the flow periodicity but also on the wave structures and propagation characteristics.